(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Endovascular therapy (EVT) has emerged as a minimally invasive approach to manage various complications associated with advanced malignancies. In palliative care, the primary goal is to alleviate symptoms, improve quality of life, and minimize procedural burden. This review discusses the role of endovascular interventions—including embolization, stenting, and catheter-based therapies—in the palliative management of cancer patients.